2016
DOI: 10.3389/fpsyg.2016.01386
|View full text |Cite
|
Sign up to set email alerts
|

The Transfer of Object Learning after Training with Multiple Exemplars

Abstract: Object recognition improves with training. This training effect only partially generalizes to untrained images of the trained objects (new exemplars, orientation,…). The aim of this study is to investigate whether and to what extent the learning transfer improves when participants are trained with more exemplars of an object. Participants were trained to recognize two sets of stimuli using a backward masking paradigm. During training with the first set, only one exemplar of each object was presented. The secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…When the stimulus set is increased, generalized strategies are involved but feature variability is necessary to make these strategies efficient. This effect of variability during training is consistent with previous studies reporting greater generalization after learning objects from different exemplars (Baeck, Maes, Van Meel, & Op de Beeck, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…When the stimulus set is increased, generalized strategies are involved but feature variability is necessary to make these strategies efficient. This effect of variability during training is consistent with previous studies reporting greater generalization after learning objects from different exemplars (Baeck, Maes, Van Meel, & Op de Beeck, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…In the absence of stimulus variability, learning remains highly specific – generally at the most specific level possible (Ahissar and Hochstein 2004). But under conditions where stimuli vary widely generalized learning can occur, e.g., when presented at multiple spatial locations or with multiple different exemplars, or when stimulus differences are relatively large, and performance levels are high (Xiao et al 2008, Wang et al 2012, Wang et al 2014, Baeck et al 2016). …”
Section: Perceptual Learningmentioning
confidence: 99%
“…Consistent with participants having superior exemplar memory in this version, it is possible that with fewer exemplars participants were simply memorizing the features of each satellite with less sensitivity to the shared structure of the categories, thereby weakening generalization. In support of this possibility, several category learning studies have demonstrated that exemplar variability is particularly important for generalization (Baeck et al, 2016;Hahn et al, 2005;Perry et al, 2010;Posner & Keele, 1968;cf. Bowman & Zeithamova, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
“…The major change in this experiment was the use of a simplified generalization paradigm which had fewer exemplars per category. Given that exemplar variability is important for generalization (Baeck et al, 2016;Hahn et al, 2005;Perry et al, 2010;Posner & Keele, 1968), it is possible that this change weakened the strength of the learned category representations, thereby weakening generalization. Another possibility is that administering additional tasks interfered with how participants were performing the generalization task.…”
Section: Time Of Day Effects On Generalizationmentioning
confidence: 99%